2018
DOI: 10.1002/pc.24878
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and energy harvesting properties of FeTiNbO6/PVDF composites with reinforced sandwich structure

Abstract: Flexible dielectrics have been the major enabler for a number of applications in advanced electronic and electrical power systems. As an important flexible dielectric material, polymer composites are promising in raising the poor dielectric properties of neat polymer of current use. In this study, a class of topological‐structure modulated multilayer composites comprising a percolation layer (FeTiNbO6[FTN]/polyvinylidenefluoride [PVDF]) intercalated between two insulating layers (PVDF or BaTiO3[BT]/PVDF) are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Surface and volume power density as shown in Table 2 are found to be remarkably high (51.12 μW/cm 2 , 2556 μW/cm 3 ). The power density obtained for PCL‐biodegradable is almost comparable to previously reported well‐known composites energy harvester 5,31‐40 …”
Section: Resultssupporting
confidence: 83%
“…Surface and volume power density as shown in Table 2 are found to be remarkably high (51.12 μW/cm 2 , 2556 μW/cm 3 ). The power density obtained for PCL‐biodegradable is almost comparable to previously reported well‐known composites energy harvester 5,31‐40 …”
Section: Resultssupporting
confidence: 83%
“…At 1 kHz, it is found that the dielectric constant of the optimum multilayer exhibits the medium value rather than the highest value and the dielectric loss of the samples is less than 0.2 in the frequency range. Normally, it is expected that the difference in conductivity and dielectric constant between BST and BT–BMZ would generate concentrated charges at the interface and thus induce dielectric constant increase as N increases. However, in real materials, the interfaces are usually not ideally sharp and local ion intermixture exists across the interfaces. In this case, as thickness of the component layer decreases, the effect of the ion intermixture at the interfaces becomes obvious and the interface polarization becomes indistinct, which finally induces the bound charge decrease and reduces the dielectric constant .…”
Section: Resultsmentioning
confidence: 99%
“…35 To obtain good piezoelectric properties and flexibility, piezo-electric composites are usually prepared by combining ceramic filler and piezoelectric polymer. 36 BaTiO 3 (BT/BTO) has attracted much attention in recent years as an easily handled and environmentally friendly inorganic filler. Among the piezoelectric composites, PVDF/BTO nanocomposites have been widely studied in energy harvesting and flexible sensors because of their simple preparation process, low cost, and good piezoelectric properties.…”
Section: Piezoelectric Materialsmentioning
confidence: 99%